FACTORS OF PROFITABILITY, SOLVENCY, LIQUIDITY, EARNINGS PER SHARE, COMPANY SIZE AND CAPITAL STRUCTURE ON STOCK PRICES IN CONSUMPTION INDUSTRY SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (Jurnal Ipteks Terapan, 2024)
AbstractCompany with focus main part sub sector industry consumption must knowing the level of financial ratios to find out whether the company's performance is running smoothly, but all of this does not have a significant impact on the share price because the profit from a share (EPS) causes an increase or decrease in the company's share price. In this research, researchers used quantitative methods. The population used was 16 companies and the sample used was 10 companies with 50 observations measured in the period 2017 - 2021. The technique used in this research is multiple linear regression analysis technique with SPSS version 20. The conclusion of this research is that Profitability does not have significant influence on share prices. Solvency does not have a significant influence on prices share. Liquidity No own influence significant to price share. Earnings per share has a significant influence on share prices. Company size does not have a significant influence on share prices. Capital structure does not have a significant influence on share prices. Simultaneously, it has a positive effect on share prices in manufacturing companies in the consumer industry sub-sector listed on the Stock Exchange Indonesia. Keywords: Profitability, Solvency, Liquidity, Earnings per Share , Company Size, Capital Structure, Share Price